How to Better Capture Women’s Agency Through Decision-making Measures : Five Tips from Research in the Philippines - World Bank (World Bank, Washington, DC, 2021)
Accurately measuring and understanding agency, or one’s ability to make choices and achieve desired outcomes can support the design and targeting of effective development interventions, as well as tracking their impacts. To maximize the effectiveness of development interventions, it is critical to understand women’s agency and how agency may influence the effectiveness of program design. Women’s decision-making in the household is frequently captured in surveys as a proxy for women’s agency. Using new analysis from a spousal survey with farming households in the Philippines, the authors explore which survey questions can accurately capture the difference in agency of women.